Code of conduct for European aquaculture. The producer's approach - Kristensen V. (Global quality assessment in Mediterranean aquaculture, 2000)
It was, in 1998, decided by Federation of European Producers (FEAP) to prepare a code of conduct. A Code of conduct to promote the responsible development and management of a viable European aquaculture sector, in order to assure a high standard of quality food production while respecting environmental considerations and consumer demands. It has been a long process, with a lot of sectors to be heard, before a document was ready to serve as a base to establish and recommend guiding principles for those in Europe who are producing live fish species through aquaculture. The goal is to establish this common base for sectional responsibility within society and demonstrate the considerations of the production sector, towards the fish it rears, the environment and the consumer. It is not a code of details, as it does not seek to distinguish between the species nor the types or scale of farms, that are encountered within the European aquaculture sector.
Workshop of the CIHEAM Networks on Technology of Aquaculture in the Mediterranean (TECAM) and Socio-Economic and Legal aspects of Aquaculture in the Mediterranean, 1999/11/29-1999/12/01, Barcelona (Spain)